The Role of National Cultures in Shaping the Corporate Management Cultures: A Four Countries Theoretical Analysis - Khan, Mohammad Ayub; Panarina, Ekaterina (Journal of Eastern European and Central Asian Research (JEECAR), 2017)
This paper studies the impact of national cultures on the management cultures of organizations. In doing so, this paper explores the differences and similarities among the national cultures of USA, Mexico, Pakistan and Russia, and subsequently analyzes the impacts of such differences and similarities on the management cultures of organizations in these countries. The findings of this study suggest that cross-cultural differences greatly influence the management culture in organizations. This finding presents cross-cultural management challenges for organizations in these countries in order to build multinational long-term strategic business partnerships.